Research Study on Technical Analysis of Selected India Private and Public Bank - Mr. Rahul Chauhan; Mr. Neel Rajpurohit (Research Parks Publishers, 2021)
Technical analysis uses historical stock statistics, usually price and volume data, to forecast future prices. In layman's terms, a technical analyst finds a pattern in a stock's data, makes the assumption that the pattern is going to repeat into the foreseeable future, and accordingly places his/her trade in the direction signaled by the pattern. Technical indicators are frequently used by technical analysts to help make their trading decisions. Popular technical indicators include moving averages, MACD, regressions, support/resistance levels, etc. Technical analysts essentially look for trends in the market. Their basic assumption is that price of a stock already has all information priced into it and that a stock is either always 'trending' up, down, or sideways. Prices move in patterns and price action repeats itself. Charts are frequently used by technical analysts to help make their trading decisions. Short term investment at the time only for useful technical analysis. Movement of the share price in the technical analysis. In other words a study of past share prices behavior to predict the future trend is termed as technical analysis. Technical analysis in the as investors buying and selling transaction at the time any kind of assumptions of for the any type of investment like market value is determined slovenly by the interaction of supply and demand, Supply and demand are governed by numerous factors both rational and irrational, Chare in trend are caused by shift in supply and demand, Some chart patterns trend to repeat themselves.